Diseño del plan de mercadeo Hostal Cheva - Paredes Vargas, Karen Emir (Universidad Antonio Nariño, 2022)
The proposal to create a marketing plan for THE CHEVA HOSTEL in the municipality of Jericó, Cheva sector was designed in order to cover the tourist market of the province of Valderrama, reaching customers through methods and digital communication, taking advantage of benefits that they are in favor of the industry like the internet. This is developed through the descriptive research method because in it the direct and indirect competences of the establishment will be studied, taking into account the data collection 10 that will be done through field work that will facilitate the proper development of the research, finally With the information already collected, strategies are formulated that can be applied in the establishment, and in turn action plans and follow-up controls are drawn up that will allow a positive approach to the marketing plan.